Heritabilitas Galur Padi Beras Hitam (Oryza sativa L) Hasil Seleksi Pedigree F1 - IGP Muliarta Aryana; Bambang Budi Santoso; AAK Sudharmawan; Muhammad Sukri (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
This study aims to determine Heritability value of F1line of black rice characters result from pedigree selection. This research conducted by field experiment carried out at the research station of Faculty of Agriculture, University of Mataram. Nyur Lembang Village, Narmada District, West Lombok Regency, NTB Province from February to June 2018. This research empioyed Randomized Complete Blok Desing (RCBD) by 40 genotipes as treatments with replications, so there are 80 of experimental units. Observed data analized by analysis of variance (ANOVA). The result of research showed that high of heritability value gained from flowering age plant height, panicle length, number of grains filled, and weight of 100 grains. Low heritability criteria are shown by number of productive tillers, number of empty grains, weight of grains per clumpsand yield (ton.ha-1)